Desenvolvimento de sistema para monitoramento e aquisição de dados microclimáticos utilizando o Programa EPICS - Marques, João Basso (2016)
This study aims at the development of instrumentation dedicated to research in Environmental Physics, comprising the alternative sensor and datalogger for measures, reading, storage and transmission of data, economically viable and open source. The EPICS program will be implemented for reading, monitoring and control sensors and microclimate research equipment. In addition, we present the development and analysis of a flexible data acquisition system that can be used for control and monitoring equipment installed in the field and in the laboratory. Also in this work, it was developed shelters for thermohigrometros, alternative temperature sensors relative humidity and temperature and heat flux in the soil, low cost and compatible with commercial sensors to search.